Monobloc Le Fort III Distraction Osteogenesis for Correction of Severe Fronto-orbital and Midface Hypoplasia in Pediatric Crouzon Syndrome. (January 2016) - Hariri, Firdaus; Cheung, Lim Kwong; Rahman, Zainal Ariff Abdul; Mathaneswaran, Vickneswaran; Ganesan, Dharmendra
In severe syndromic craniosynostosis, distraction osteogenesis (DO) provides superior segmental advancement and allows progressive clinical monitoring to ensure that adequate skeletal expansion is achieved. We report two cases of Crouzon syndrome involving a 3-year-old boy and a 4-year-old girl, who were both treated with monobloc Le Fort III DO using a combination of external and internal distraction devices (Synthes, Oberdorf, Switzerland) to treat severe orbital proptosis and obstructed nasopharyngeal airway secondary to severe hypoplastic craniofacial skeletal components. Their skeletal segments were advanced in daily increments by 27 mm and 23 mm, respectively. Results at 18 months postoperatively showed successful outcomes, as evidenced by adequate eye protection, tracheostomy tube decannulation following objective evidence of patent nasopharyngeal airway, and acceptable facial appearance. Monobloc Le Fort III DO using a combination of external and internal devices produces favorable functional and clinical outcomes for the treatment of severe orbital and airway discrepancy in Crouzon syndrome.